From syllabi to startups: lessons from eight African case studies on university-industry collaboration and agri-entrepreneurship education - Chfadi, Tarik; Abdulkader, Bisan; Chirinda, Ngonidzashe (Frontiers in Sustainable Food Systems, 2025)
Agriculture is an important component of the African economy, contributing to growth and employment. Still, African agriculture remains plagued by problems linked to limited modernization, low productivity, and an aging farmer population, and declining interest of young people. To remedy this situation, the AgriENGAGE project, a European Commission-funded initiative involving eight African and two European universities, seeks to improve agricultural education and stimulate entrepreneurship in African universities. Interviews and reports by these universities highlight the four essential elements: the need to find the right balance between theory and practice, the role of practical learning and incubation, the place of public support, and the need for industry involvement. Despite the efforts made, including AgriENGAGE, several problems persist, such as the limited space and economic literacy in the teaching community, the lack of resources and infrastructure, and the limited collaborations between academic institutions and industry.